Ischemic oculomotor nerve palsy due to hyaluronic acid filler injection. (1st April 2018) - Bae, In Ho; Kim, Min Sung; Choi, Hoon; Na, Chan Ho; Shin, Bong Seok
Summary: Hyaluronic acid (HA) is the most popular agent today for intradermal injections to improve wrinkles and other cosmetic defects. Ischemic necrosis due to injection of HA is one of the serious complications. Because there are many vascular branches around the nose, caution and care should be given during facial filler injection. Although the incidence is rare, blindness and permanent visual loss may occur. We describe a 29‐year‐old woman presented with painful erythematous swelling with violaceous patch on right periocular area and glabella after HA filler injection. After injecting the filler, she felt pain and dizziness, and her vision became blurred. She immediately received hyaluronidase around the HA filler inject area and during hospitalized for 10 days, she was successfully treated with systemic steroid, vasodilator, prophylactic antibiotics, and LLLT (low‐level laser therapy) without any defects.